Belize. Annual report 2009 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The 2009 Annual Report presents the contributions that the Institution has made towards the development of the agriculture sector and rural prosperity in Belize durin 2009. This annual report was developed with stakeholder's participation and compliments IICA's hemispheric and regional work plans . This report is also in compliance with IICA accountability to its stakeholders to inform of our interventions , partnerships and future actions to ensure consistent advances in the agriculture sector.